THE DERMO-EPIDERMAL INTERFACE IN LICHEN-PLANUS END LUPUS-ERYTHEMATOSUS - Marren, P; Deberker, D; Wojnarowska, F; Davies, M; Leigh, I; Burge, S (1994)
The pathogenesis of lichen planus (LP) and cutaneous lupus erythematosus (LE) was investigated by immunohistochemical staining of skin biopsies from eight patients with these conditions compared with controls. Monoclonal antibodies were directed against antigens of the various components of the basement membrane zone. We found a differential, site specific response by these components to the inflammatory process. The structural collagens in the basal lamina underwent a primarily reparative response demonstrated by thickening and reduplicatian, whilst an epidermal, hemidesmosome-associated antigen was consistently disrupted and fragmented. Despite diverse clinical features there were similarities between these two diseases suggesting some common pathogenic mechanisms.